The second expression is easily solved by dividing each term by `-4y^2`
`(y^4-12y^3-4y^2)/(-4y^2) =(y^4)/(-4y^2) -(12y^3)/(-4y^2) -(4y^2) /(-4y^2)=-1/4y^2+3y+1`
You can also express it in vertex form:
`1/2yh=3 -gt h=6`
`-1/4(6)^2+k=1 - gtk=9+1=10`
We will use long division to solve the third expression:
2x^2+ 5x + 4
The 4th expression can also be solved using long division.
As for the first expression, neither the numerator nor the denominator can be factored in such a way as to simplify the expression, and as such, writing it in a different form is a fruitless exercise.